Population Pharmacokinetic Analysis of Bedaquiline‐Clarithromycin for Dose Selection Against Pulmonary Nontuberculous Mycobacteria Based on a Phase 1, Randomized, Pharmacokinetic Study. (12th June 2021) - Kurosawa, Ken; Rossenu, Stefaan; Biewenga, Jeike; Ouwerkerk‐Mahadevan, Sivi; Willems, Wouter; Ernault, Etienne; Kambili, Chrispin
Abstract: Based on the in vitro profile of bedaquiline against mycobacterial species, it is being investigated for clinical efficacy against pulmonary nontuberculous mycobacteria (PNTM). Being a cytochrome P450 3A substrate, pharmacokinetic interactions of bedaquiline are anticipated with clarithromycin (a cytochrome P450 3A inhibitor), which is routinely used in pulmonary nontuberculous mycobacteria treatment. This phase 1, randomized, crossover study assessed the impact of steady‐state clarithromycin (500 mg every 12 hours for 14 days) on the pharmacokinetics of bedaquiline and its metabolite (M2) after single‐dose bedaquiline (100 mg; n = 16). Using these data, population pharmacokinetic modeling and simulation analyses were performed to determine the effect of clarithromycin on steady‐state bedaquiline exposure. Although no effect was observed on maximum plasma concentration of bedaquiline and time to achieve maximum plasma concentration, its mean plasma exposure increased by 14% after 10 days of clarithromycin coadministration, with slower formation of M2. Simulations showed that bedaquiline plasma trough concentration at steady state was higher (up to 41% until week 48) with clarithromycin coadministration as compared to its monotherapy (400 mg once daily for 2 weeks, followed by 200 mg 3 times a week for 46 weeks; reference regimen). The overall exposure of a simulated bedaquiline regimen (400 mg once dialy for 2 weeks, followed by 200 mg twice a week for 46 weeks) with clarithromycin was comparable (<15% difference) to the monotherapy. Overall, combination of bedaquiline (400 mg once daily for 2 weeks, followed by 200 mg twice a week for 46 weeks) with clarithromycin seems a suitable regimen to be explored for efficacy and safety against pulmonary nontuberculous mycobacteria.